ESTABLISHING THE EFFECTIVENESS OF AN ACUTE CARE FOR ELDERS (ACE) STRATEGIC DELIVERY MODEL - Sinha, S. (Innov Aging, 2017)
The Acute Care for Elders (ACE) Strategy recognizes the high-risk environment of the acute care hospital setting to all persons aged 65+. This population accounts for 42% of hospital admissions and 58% of overall hospital days in Ontario. We wanted to determine the effectiveness of a multi-component ACE Strategy to impact patient and system outcomes for older adults admitted to the general medicine wards from April 1, 2009 to March 31, 2014. A quasi-experimental time series analysis was conducted on the outcomes of 9,595 patient admissions. Results showed there was a 27.8% decrease in mean length of stay, 23.8% decline in the ALOS/ELOS ratio, and a 13.4% decline in readmissions with an 11% increase in the number of older patients being able to return home after discharge. This Strategy demonstrates the benefits from linking multiple evidence-informed models across the continuum of care in achieving patient and system outcomes.